PENGARUH KEPEMILIKAN MANAJERIAL, PERTUMBUHAN PERUSAHAAN DAN FREE CASH FLOW TERHADAP KEBIJAKAN UTANG - Yuliana Rezki; Hairul Anam (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2020)
This resaerch aims to examine whether Managerial Ownership, Company Growth and Free Cash FlowÂ  influence The Debt Policy of Food and Beverage companies on the Indonesian stock exchange. The sampling used side by side methods during the 2013 to 2017 research period, and a sample of 4Â  companies was obtained from 18 company populations.. The analytical method used in this research is multiple linear regression.The results of this research indicate that Managerial Ownership variables have an effect on Debt Policy, while Company Growth and Free Cash Flow variables have no effect on Debt Policy in the Indonesian Stock Exchange Food and Beverage Companies.